Promoting CEA agricultural exports through association agreements with the EU: why it is not working - Klaus Frohberg; Monika Hartmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1997)
This paper analyzes why the Association Agreements between the Central and Eastern European countries, referred to as Central European Associates (CEAs), and the European Union (EU) have failed with respect to agriculture. In the first part of the paper the development and importance of agricultural trade in the CEAs is described. It is shown that the EU is the most important trading partner in agricultural and food products for the CEAs. However, in recent years the trade balance for agricultural and food products between these countries and the EU has changed in favor of the latter; this is contrary to the aim of these agreements. Important external and internal factors determining trade relations between the EU and the CEAs are identified and discussed in the second half of the paper. These include the development of the real exchange rates, restrictions in the levels of domestic production, inadequate food quality compared to EU products, and insufficient sanitary standards in and a lack of competitiveness of the processing industry. These factors offset agricultural and food policies which have been aimed at protecting and supporting agriculture and the food processing industry in all CEAs but Bulgaria and Romania. In the last two countries, agricultural and food policies have primarily protected consumers at the expense of these two sectors. – – Die Assoziierungsabkommen zwischen den Mittel- und Osteuropäischen Ländern (MOEL) und der Europäischen Union haben im landwirtschaftlichen Bereich nicht den erhofften Erfolg gebracht. Der vorliegend Beitrag untersucht die Gründe für dieses partielle Scheitern. Im ersten Teil des Papiers wird die Entwicklung und Bedeutung des Agrarhandels der MOEL beschrieben. Dabei zeigt sich, daß die EU für die meisten MOEL im Agrarbereich der wichtigste Handelspartner ist. Die Handelsbilanz für Agrar- und Ernährungsgüter zwischen den MOEL und der EU hat sich in den letzten Jahren jedoch zu Gunsten der Europäischen Union verändert; eine Entwicklung, die dem Ziel der Assoziierungsabkommen widerspricht. Wichtige externe und interne Faktoren, die die Handelsbeziehungen zwischen der EU und den Assoziierungsländern bestimmen, werden im zweiten Teil des Beitrags aufgezeigt und diskutiert. Hierzu gehören die Veränderung der Realen Wechselkurse, Begrenzungen in der inländischen Agrarproduktion, unzureichende Nahrungsmittelqualität im Vergleich zu den in der EU erzeugten Produkten, unzureichende sanitäre und phytosanitäre Standards und mangelnde Wettbewerbsfähigkeit in der Verarbeitungsindustrie. Diese Faktoren können auch nicht durch die Agrarpolitik dieser Länder kompensiert werden, die mit Ausnahme von Bulgarien und Rumänien in allen Assoziierungsländern auf einen Schutz des landwirtschaftlichen Sektors ausgerichtet ist.
urn:nbn:de:gbv:3:2-22602
Keywords: 330; Agraraußenhandel; Assoziierung; Internationaler Wettbewerb; Landwirtschaft; EU-Staaten; Osteuropa